Influence of A Polymer Preparation on Growth And Development During Vegetative Reproduction of Mulberry - Raxmonberdiyev Vaxobdjon Karimovich; Matmurotov Baxtishod Yangiboyevich; Mansurova Fotimoa Asilxo‘ja qizi; Ibragimov Tursun Shopo‘lat o‘g‘li (Zien Journals, 2023)
The article studies the cultivation of seedlings from varietal cuttings of mulberry in the conditions of the Tashkent region and the acceleration of the growth and development of cuttings of mulberry by applying a polymer preparation to the cuttings of the cultivated mulberry tree when laying bush plantations, which allows satisfying the needs for feeding the silkworm.
Keywords: Mulberry; cuttings; growth and development; root